THE ANALYSIS OF FINANCIAL PERFORMANCE IN RISK SYSTEMATIC AND RETURN STOCK FOR MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK SHARIAH INDEX (ISSI) - Ramdani Abdullah Mukhyi; Hwihanus Hwihanus; Tri Ratnawati (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
The purpose of this research is to examine and analyze the effect of financial performance(liquidity, activity, leverage, growth, and profitability) on the systematic risk and return ofIslamic stocks in the Indonesian Islamic stock index. This research data is gathered from annualreports on manufacturing companies within the year 2017-2019. This research population is allmanufacturing companies listed in the Indonesian Shariah Stock Index for the period 2017-2019 by using the purposive sampling method. The research technique used is a regressionwith Structural Equal Model Partial Least Square (SEM-PLS) consists of Inner model, Outersmodel, and Weight relation. The test results showed that all tested variables were influencedby other variables and were significant except Liquidity against systematic risk. And Leverageagainst systematic risk showing that liquidity, Leverage, Profitability have a not significanteffect on the systematic risk structure is rejected whereas hypotheses other research accepted